Republic of Korea : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Korea. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that Korea's growth has slowed after decades of impressive economic progress. The economy is facing a number of structural headwinds, including unfavorable demographic developments, heavy export reliance, pockets of corporate vulnerability, labor market distortions, lagging productivity, and high household debt. Inequality and poverty are also of concern. Growth is projected to tick up to 2.7 percent in 2016 and 3.0 percent in 2017, with inflation remaining subdued. Credit is expected to continue to grow, partly reflecting the impact of interest rate cuts, but at a slower pace consistent with the tightening of prudential measures and the envisaged moderation in construction investment after 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet